Semi-analytical modeling and experimental verification of a flexible varying section disk–blades system with elastic supports. (April 2023) - Guo, Xumin; Zeng, Jin; Ma, Hui; Liu, Shiyu; Luo, Zhong; Li, Chaofeng; Han, Qingkai; Wen, Bangchun
Abstract: A semi-analytical model of a flexible varying section disk–blades (FVSDBs) system with elastic supports is proposed, where the spin softening, centrifugal stiffening, and Coriolis force effects of the system are considered. Timoshenko beams with a stagger angle are used to simulate blades, and a varying section wheel based on plate theory is used to construct the disk. Hamilton's principle and Galerkin method are utilized to derive the differential governing equations of the FVSDBs system. The proposed semi-analytical model accounts for the lateral vibration of the disk, and the longitudinal and lateral vibration of the blades. Besides, the validity of the proposed model has been verified by comparing the natural frequencies, mode shapes, and vibration responses obtained from the proposed model, finite element model (FEM), and experiment. The results indicate that the proposed semi-analytical model has high precision and computational efficiency, which can provide an alternative scheme for predicting the vibration characteristics of varying section disk–blades and overcoming the high computational cost of finite element models. Graphical abstract: Highlights: A dynamic model of the FVSDBs is developed by semi-analytical method. The varying section and elastic supports characteristics of disk–blades are considered. The proposed model is verified by FEM and experiment.